Pengaruh Faktor Determinan terhadap Hasil Terapi Hipertensi Pasien pada Tiga Puskesmas di Jakarta Pusat - Pertiwi, Andam Dewi; Sarnianto, Prih; Ramadaniyati, Hesti Utami (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2019)
Hypertension has been known as risk factor of cardiovascular diseases necessitating the good control of blood pressure. The evident also shows the increased number of uncontrolled hypertensive patients. This study aimed to identify the determinants of controlled blood pressure in primary health centre hypertensive patients. The benefits of this research is to educated to public about factors that influence hypertension controlled. This research lasted for five months was conducted through patient interview of respondents meeting inclusion criteria in three primary health centres/PHC (PHC Menteng, PHC Tanah Abang, and PHC Johar Baru). Some data of the interview were validated by reviewing patient?s medical record. There were 26 factors used to analyse the determinants which included sociodemographic, biophysiology, dietary consumption patterns, use of hormonal contraceptives, physical activity, and stress). The result of multivariate regression analysis revealed two significant determinants, namely the presence of cardiovascular diseases (odd ratio/OR = 0,091, P-value = 0,004) and physical activity (OR = 10,647, P-value = 0,002). Patients with history of cardiovascular disease had 10,99 times risk to experience uncontrolled hypertension compared with those with no history of the disease. In addition, patients with routine physical activity at least 5 days/week (150 minutes/week) were 10,647 times to have controlled blood pressured as opposed to their counterpants.